The atorvastatin goal achievement across risk levels: (ATGOAL) study in Thailand - Chaicharn Deerochanawong (2018)
Objective: To evaluate the efficacy and safety of atorvastatin at the starting doses of 10, 20, 40 mg and evaluate the effectiveness of 1 step titrate up regimen. Material and Method: Two hundred and forty two subjects with dyslipidemia were enrolled and assigned the appropriate dose in relation to their individual cardiovascular risk status and baseline LDL-C levels. If the NCEP targets were not achieved, the doses were titrated up at week 4 and the primary efficacy was evaluated at week 8. Results: A majority of subjects (88.8%) achieved their LDL-C goals at week 8. Almost all of the subject's LDL-C levels reached their goals by week 2 and 4 (81.6% and 87.1%, respectively). Only 10.7% (n=25) required the sole titration. Each dose provided significant decreases in LDL-C (average -46.4%). Only 36 subjects experienced treatment related adverse events, the majority of these were in the high-risk group (n=22) with only one subject registering a serious adverse event. Conclusion: Atorvastatin is effective and safe for Thai patients with dyslipidemia. The appropriate starting dose has contributed in the achievement of cholesterol reduction.